Konstruk Teoritis dan Pengukuran Kepemimpinan Profetik - Budiharto, Sus; Himam, Fathul (Faculty of Psychology, Universitas Gadjah Mada, 2006)
Considering the increased concerns related to the issues of moral and spiritual leadership, I conducted two studies to develop the construct and measure of prophetic leadership. In the first study, three Indonesian Moslem leaders were interviewed to describe their leadership behavior and characteristics from their own praxis. Prophetic leadership is the ability to influence others accomplishing shared objectives that is reinforced by soul enlightenment as the prophets have shown in their time. In the second study, 40 items were generated for measuring prophetic leadership were administrated to 151 employee of Islamic University of Indonesia. The dimensions that represent prophetic leadership consist of sidiq (conscience centred), amanah (trustworthy and highly committed), tabligh (communication skills), and fathonah (problem solver). The construct is translated into a measure called prophetic leadership scale. The results show an empirical support for its construct validity. A positive significant intercorrelations among four dimensions were found. Items were loaded into four different mentioned dimensions. Practical implications and suggestions for future research are discussed. Keywords: Prophetic leadership, sidiq, amanah, tabligh, fathonah